THE EFFECT OF PUBLIC SAVINGS AND DEPOSITS TOWARD CREDIT LENDING DURING PANDEMIC - hubert, florencia hubert (PROCEEDING INTERNATIONAL BUSINESS AND ECONOMICS CONFERENCE (IBEC), 2022)
Bank’s function to collect funds and provide loans to the public, therefore banks also need funds to carry out their functions. This research uses descriptive research method and purposive sampling technique. Data analysis used in this research are descriptive statistical test, normality test, heteroscedasticity test, multicollinearity test, autocorrelation test, multiple linear analysis test, t test, F test and coefficient of determination test. Based on the results of the research show that public saving has no effect and significant on lending, this can be seen from the results of partial hypothesis testing (t test) which shows tcount < ttable, namely -4.551 < 2.0243 and significant value < 0.05, namely with a value of 0.000 < 0.05. Based on this, the first hypothesis (H1) is rejected. Deposits have a significant effect on lending, this can be seen from the results of partial hypothesis testing (t test) which shows tcount > ttable, namely 13,398 > 2.0243 and significant value < 0.05, with a value of 0.000 < 0.05. Based on this, the second hypothesis (H2) is accepted. Community and deposits have a significant effect on lending, this can be seen from the results of simultaneous hypothesis testing (F test) which shows Fcount (166.311) > Ftable (3.25) with a significance of 0.000 <0.05, it can be interpreted that the third hypothesis (H3) accepted in other words, public savings and time deposits have a significant effect on lending simultaneously. Based on this, the third hypothesis (H3) is accepted.